Description of two new species of Rhamphus related to R. oxyacanthae (Curculionidae, Curculioninae, Rhamphini) from Italy based on a morphological study supported by molecular data - Diotti, Luciano; Caldara, Roberto; Toševski, Ivo (Zootaxa, 2021)
Two new species of the weevil genus Rhamphus from Italy are herein described: R. bavierai n. sp. (Sicily) and R. hampsicora n. sp. (Sardinia). Both are morphologically and from a molecular perspective close to R. oxyacanthae (Marsham, 1802) and R. monzinii Pesarini & Diotti, 2012. Aside from a diagnostic description and a synoptic key, distribution data and notes on the host plants of the four species are reported. Whereas R. monzinii can be distinguished by several morphological characters, the other three species are morphologically very similar to each other and separable only by the combination of a few subtle characters. On the contrary, a preliminary molecular study revealed substantial divergences of mtCOI from 6.2 to 14.9% between the species, confirming the importance of an integrative taxonomy.